THE DEVELOPMENT OF MATHEMATICAL SPEECH OF FUTURE TEACHERS IN THE STUDY COURSE METHODOLOGY OF MATHEMATICS - Sergeeva, Larisa; Ledovaya, Alina (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2017)
The article is devoted to setting forth of the urgent problem of the cultural development of mathematical speech of future teachers. The article shows the study of mathematical concepts by students taking into account specialized language of the mathematics as one of the aspects of this problem. The proposed method of development of mathematical speech is based on the constructed hierarchy of mathematical concepts consideration the specifics of mathematical objects’ nature and characteristics of the used mathematical language. The conducted research allowed to establish the influence of the created active studying for developing students' methodological speech, cognitive motives, interest in future professional activity.